Copper ammonia pure cotton composite fiber and non-woven fabric and preparation method thereof

By using the combination of cuproammonia pure cotton composite fiber and other fibers, combined with special pretreatment and hydrospuncture processing technology, the problem of poor continuity of facial mask non-woven fabrics during hydrospuncture production is solved, and high water absorption and softness are prepared. Non-woven fabric with breathable and strong antibacterial properties.

CN119465513APending Publication Date: 2025-02-18SHANGHAI JISUO IND CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411636141.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

Smart Images

  • Figure BDA0005137195900000051
    Figure BDA0005137195900000051
  • Figure BDA0005137195900000052
    Figure BDA0005137195900000052
  • Figure BDA0005137195900000061
    Figure BDA0005137195900000061
Patent Text Reader

Abstract

The invention relates to the technical field of non-woven fabric spinning, in particular to a copper ammonia pure cotton composite fiber and a non-woven fabric and a preparation method thereof. The copper ammonia pure cotton composite fiber comprises 50% of pure cotton fiber and 50% of copper ammonia fiber, and the pure cotton fiber is prepared by the following steps: immersing the pure cotton fiber in a mixed solution of isopropanol and bromoethanol, and irradiating for 2 hours under an ultraviolet lamp; the irradiated pure cotton fibers are fished out and drained, and the drained pure cotton fibers are exposed to gamma rays to be irradiated for 30 s. The non-woven fabric is prepared from copper ammonia pure cotton composite fibers. The preparation method of the copper ammonia pure cotton composite fiber non-woven fabric comprises the preparation steps of raw material preparation and fiber treatment, spunlace reinforcement treatment and post-treatment. Through a special pretreatment process, the composite fibers have high water absorption rate, meanwhile, the combining capacity with other fibers is enhanced, the three-dimensional irregularly-arranged fiber structure is adopted, the stability and integrity of the non-woven fabric structure are guaranteed, and the phenomenon that the non-woven fabric is mixed with water to form paste is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nonwoven textile technology, and in particular to a copper-ammonia pure cotton composite fiber and a nonwoven fabric thereof and a preparation method thereof. Background Art

[0002] As a skin care product, facial mask is applied on the face to achieve beauty effects. The matrix of the mask, that is, the carrier of the mask, is crucial to the effect of the mask and user experience. In recent years, non-woven fabrics, as a new type of textile material, have been widely used in the field of mask matrices.

[0003] In order to obtain a higher moisture absorption rate, the mask non-woven fabric in the related art often uses carboxymethyl cellulose fiber as the preparation raw material. However, when actually produced by the water spunlace method, the carboxymethyl cellulose fiber tends to form a paste after mixing with water, so the continuity of production cannot be guaranteed. To solve this problem, a cuprammonia pure cotton composite fiber, a non-woven fabric and a preparation method thereof are provided. The non-woven fabric has a moisture absorption rate equivalent to that of the carboxymethyl cellulose non-woven fabric. Summary of the invention

[0004] In view of the above-mentioned deficiencies, the present application provides a cuprammonia pure cotton composite fiber, a non-woven fabric and a preparation method thereof, aiming to achieve: without using carboxymethyl cellulose fiber, a highly hydrophilic fiber as a raw material, and using a hydroentanglement production condition to obtain a non-woven fabric with a higher water absorption rate, and the phenomenon of the fiber raw material forming a paste after mixing with water will not occur, thereby ensuring the continuity of production.

[0005] In the first aspect, the present application provides a copper-ammonia pure cotton composite fiber and a non-woven fabric thereof using the following technical solutions: A copper-ammonia pure cotton composite fiber comprises the following components in percentage by mass: 50% pure cotton fiber and 50% copper-ammonia fiber, wherein the pure cotton fiber is prepared by the following pretreatment process: S1. Immerse the pure cotton fiber in a mixed solution of isopropyl alcohol and bromoethanol and irradiate it under ultraviolet light for 2 hours; S2. After the irradiation, the pure cotton fiber is fished out and drained, and then exposed to gamma rays for 30 seconds.

[0006] By adopting the above technical solution: after the pure cotton fiber treated by a special pretreatment process is mixed with the cuprammonia fiber to form a composite fiber, it has a higher water absorption rate and its bonding ability with other fibers is also enhanced.

[0007] A non-woven fabric, the raw materials for preparing the non-woven fabric include the copper-ammonia pure-cotton composite fiber.

[0008] Preferably, the nonwoven fabric is made from the following raw materials: 25-30% soybean protein fiber, 60-70% cuprammonia pure cotton composite fiber, and the remainder is antibacterial zeolite fiber.

[0009] By adopting the above technical solution: the prepared non-woven fabric not only has excellent water absorption performance, but also has soft texture, good air permeability, and also has antibacterial function.

[0010] Preferably, the specification of the soybean protein fiber is 1.4dtex*40mm, the specification of the cuprammonia pure cotton composite fiber is 1.6dtex*55mm, and the specification of the antibacterial zeolite fiber is 1.2dtex*35mm.

[0011] By adopting the above technical solution: refining and proportioning the specifications of the three fibers, a non-woven fabric with better performance and more stable structure can be prepared.

[0012] In a second aspect, the present application provides a method for preparing a non-woven fabric, which adopts the following technical solution: A method for preparing a nonwoven fabric, the preparation steps are as follows: A1. Prepare the copper-ammonia pure cotton composite fiber, soybean protein fiber and antibacterial zeolite fiber, and then put them into the opening and mixing machine according to the proportion. After loosening and mixing, put them into the carder for proper carding, and then blow them with strong airflow to form an air duct, so that the various fibers on the carder are peeled off, arranged in three-dimensional irregular patterns and deposited on the net curtain to form a fiber web; A2: The fiber web is pre-humidified and then placed in the spunlace processing area, and is reinforced and entangled through the first, second and third stage spunlace; A3: Dehydrate the spunlace treated fiber web and then dry it.

[0013] By adopting the above technical solution: the excellent properties of cuprammonia pure cotton composite fiber, soybean protein fiber and antibacterial zeolite fiber can be fully utilized to prepare non-woven fabric products with high water absorption, strong antibacterial properties, soft texture and environmental protection, and the production can be continuous and stable when using the hydroentanglement method.

[0014] Analysis of the possible reasons: In step A1, a strong airflow is used to form an air duct, so that the copper-ammonia pure cotton composite fiber, soybean protein fiber and antibacterial zeolite fiber are arranged three-dimensionally and deposited on the mesh curtain. This irregularly arranged fiber structure makes the non-woven fabric have a larger surface area and more water absorption channels, thereby improving its water absorption performance. At the same time, due to the interweaving and entanglement between the fibers, the non-woven fabric can maintain the stability and integrity of its structure while maintaining a high water absorption rate, avoiding the phenomenon of forming a paste after mixing with water; In addition, the choice of raw materials also has an important impact on the performance of non-woven fabrics. Copper-ammonia pure cotton composite fiber has high water absorption and hydrophilicity, and can quickly absorb and lock moisture; soybean protein fiber has good biocompatibility and hygroscopicity, which can further improve the comfort and water absorption performance of non-woven fabrics; antibacterial zeolite fiber gives non-woven fabrics excellent antibacterial properties, and its unique fiber structure also helps to enhance the overall stability of non-woven fabrics.

[0015] The spunlace liquid used in A2 is a mixed liquid with a volume ratio of polyoxyethylene ether: water = 2:3.

[0016] By adopting the above technical solution, the wettability and permeability of the water flow can be significantly improved, so that the spunlace liquid can better penetrate into the interior of the fiber web, thereby enhancing the entanglement and connection between the fibers.

[0017] Preferably, in A2, the first stage of hydroentanglement is drum hydroentanglement, the second stage of hydroentanglement is drum hydroentanglement, and the third stage of hydroentanglement is flat mesh hydroentanglement.

[0018] By adopting the above technical solution: the rotary drum hydroentanglement can effectively entangle and reinforce the fibers in the fiber web with its high-speed rotating drum surface and water jet. The continuous use of rotary drum hydroentanglement in the first and second stage hydroentanglement can ensure that the connection between the fibers is tighter, thereby improving the strength and stability of the non-woven fabric; The third stage uses flat mesh spunlace to further optimize the structure and performance of the fiber web. With its large mesh surface and steady water flow, the flat mesh spunlace can evenly impact and reinforce the fiber web, making the fiber distribution more uniform, reducing the thickness difference of the fiber web, and further improving the water absorption performance of the non-woven fabric; At the same time, this combination method can also ensure the continuity of production. The alternating use of rotary drum spunlace and flat net spunlace can reduce the problems of fiber web damage or uneven entanglement that may be caused by a single spunlace method, thereby improving production efficiency and product quality and ensuring the water absorption rate of the non-woven fabric.

[0019] Preferably, in A2, the first-stage hydroentanglement pressure is 6.5-8.5 MPa, the second-stage hydroentanglement pressure is 15-20 MPa, and the third-stage hydroentanglement pressure is 10-12 MPa.

[0020] By adopting the above technical solution: this pressure setting method not only takes into account the reinforcement needs of the fiber web, but also takes into account the integrity and water absorption performance of the fiber, thereby achieving the advantages of high water absorption, stable structure and production continuity of non-woven fabrics.

[0021] The non-woven fabric prepared by the above-mentioned method for preparing the non-woven fabric is used in the preparation of medical wound dressings and facial mask base fabrics.

[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application uses a special pretreatment process to make the composite fiber formed by mixing pure cotton fiber and cuprammonia fiber have a higher water absorption rate, while enhancing the ability to combine with other fibers, and adopts a three-dimensional irregularly arranged fiber structure. The interweaving and entanglement between the fibers ensure the stability and integrity of the non-woven fabric structure, and avoid the phenomenon of forming a paste after mixing with water; 2. This application uses a mixture of cuprammonia pure cotton composite fiber, soybean protein fiber and antibacterial zeolite fiber to prepare a non-woven fabric that not only has excellent water absorption performance, but also has soft texture, good air permeability and antibacterial function. The addition of soybean protein fiber further improves the comfort and water absorption performance of the non-woven fabric, while the antibacterial zeolite fiber gives it excellent antibacterial performance; 3. This application selects cuprammonia pure cotton composite fiber, soybean protein fiber, etc. as raw materials, which not only makes the product have excellent performance, but also meets the requirements of environmental protection and sustainability. These fibers are widely available and renewable, which reduces the burden on the environment and conforms to the current concept of green development. DETAILED DESCRIPTION

[0023] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.

[0024] Preparation Example 1 A copper-ammonia pure cotton composite fiber, which is composed of the following components by mass percentage: 50% pure cotton fiber and 50% copper-ammonia fiber, wherein the pure cotton fiber is prepared by the following pretreatment process: S1. Immerse the pure cotton fiber in a mixed solution of isopropyl alcohol: bromoethanol = 7:3 by volume, and irradiate it under ultraviolet light for 2 hours; S2. After the irradiation, the pure cotton fiber is fished out and drained, and then exposed to gamma rays for 30 seconds.

[0025] Preparation Example 2 A cuprammonia pure cotton composite fiber, which differs from Preparation Example 1 in that, by mass percentage, it is composed of the following components: 70% pure cotton fiber and 30% cuprammonia fiber.

[0026] Preparation Example 3 A cuprammonia pure cotton composite fiber, which differs from Preparation Example 1 in that, by mass percentage, it is composed of the following components: 30% pure cotton fiber and 70% cuprammonia fiber.

[0027] Preparation Example 4 A cuprammonia pure cotton composite fiber, which differs from Preparation Example 1 in that, by mass percentage, it is composed of the following components: 50% pure cotton fiber and 50% cuprammonia fiber, wherein the pure cotton fiber is ordinary pure cotton fiber and is not processed by a pretreatment process.

[0028] Performance testing 1. Liquid absorption test The liquid absorption of the prepared sample was tested according to the test standard GB / T 24218.6-2010 "Test methods for nonwoven fabrics for textiles - Part 6: Determination of absorbency". An area of ​​150mm*150mm was selected from the side and center of the same sample, and the sample was cut into 5 pieces. The 5 samples were tested and the average value of the test results was taken.

[0029] 2. Air permeability test The air permeability of the prepared samples was tested according to the test standard GB / T 24218.15-2018 "Test methods for textile nonwovens Part 15: Determination of air permeability". 150mm*150mm areas were selected from the side and center of the same sample, and the 5 samples were cut into 5 pieces. The pressure difference of the airflow of the vacuum pump on the upper and lower surfaces of the sample was 200Pa, and the circular test area of ​​the test head was 20cm 2 , the test results are averaged. Example

[0030] Examples 1-4 A cuprammonia pure cotton composite fiber nonwoven fabric is composed of the following components and is prepared by the following steps: A1. Prepare the copper-ammonia pure cotton composite fiber, soybean protein fiber and antibacterial zeolite fiber prepared in Preparation Example 1, and then put them into an opening and mixing machine according to a certain proportion. After being loosened and mixed, put them into a carder for proper carding, and then blow them with a strong airflow to form an air duct, so that the various fibers on the carder are peeled off, arranged in a three-dimensional irregular manner and deposited on a mesh curtain to form a fiber web; Among them, the specifications of soybean protein fiber are 1.4dtex*40mm, the specifications of cuprammonia pure cotton composite fiber are 1.6dtex*55mm, and the specifications of antibacterial zeolite fiber are 1.2dtex*35mm; A2: pre-humidifying the fiber web, and then placing it in the spunlacing processing area, and strengthening the entanglement through the first rotary drum spunlacing, the second rotary drum spunlacing, and the flat net spunlacing; The first rotary drum spunlace pressure is 6.5MPa, the second rotary drum spunlace pressure is 15MPa, the flat mesh spunlace pressure is 10MPa, and the spunlace liquid is a mixed liquid of polyoxyethylene ether: water = 2:3 by volume ratio; A3: Dehydrate the spunlace treated fiber web, and then dry it at 90°C. The moisture content after drying is 1.5%.

[0031] Table: Components and dosages in nonwoven fabrics of Examples 1-4 (%) Comparative Example 1 A cuprammonia pure cotton composite fiber nonwoven fabric, which is different from Example 1 in that, in preparation step A1, multiple fibers on a carder are peeled off, and the fibers are arranged and deposited on a mesh curtain by cross-laying to form a fiber web.

[0032] The samples prepared in Examples 1-4 and Comparative Example 1 were taken and tested for liquid absorption and air permeability according to the above test standards, and the test results were averaged.

[0033] Table: Performance test results of Examples 1-4 As can be seen from the above table, the samples prepared by Examples 1-4 have a liquid absorption capacity of 14.2-14.8 times and an air permeability of 2234-2247 mm, indicating that the cuprammonia pure cotton composite fiber non-woven fabric has a high water absorption rate, which is equivalent to or even better than that of the carboxymethyl cellulose fiber non-woven fabric, and does not become a paste when using the water spunlace production process.

[0034] The reasons may be as follows: the special pretreatment process is an important prerequisite for the outstanding performance of this non-woven fabric. The pretreatment process may involve specific treatment of pure cotton fibers, such as surface modification or chemical treatment, to enhance the fiber's hygroscopicity and ability to combine with other fibers. This pretreatment ensures that the composite fiber can give full play to its performance advantages when forming a non-woven fabric, and effectively reduces the risk of the fiber swelling and becoming a paste due to contact with water; Moreover, the three-dimensional irregularly arranged fiber structure has a positive effect on the performance of non-woven fabrics. This structure not only increases the degree of interweaving and entanglement between fibers, improves the overall stability and integrity of the non-woven fabric, but also forms effective channels and gaps, which is conducive to the rapid absorption of liquids and the smooth flow of gases.

[0035] As for Comparative Example 1, the test results show that the liquid absorption is 13.9 times and the air permeability is 2226mm. Compared with Example 1, all the properties are slightly decreased. It adopts a cross-laying method instead of a random web method. The random web method can make the fibers more evenly distributed and form a denser fiber network, which is conducive to liquid absorption and gas circulation. Cross-laying may make the fibers sparsely distributed in some areas, resulting in a slight decrease in the liquid absorption and air permeability of the non-woven fabric. In addition, cross-lamination may lead to a decrease in the degree of interweaving and entanglement between fibers. The interweaving and entanglement between fibers are crucial to the performance of non-woven fabrics. They can enhance the structural stability and liquid absorption capacity of non-woven fabrics. If the degree of interweaving and entanglement is insufficient, the structure of the non-woven fabric will be easily damaged when subjected to external force or liquid impact, thus affecting its performance.

[0036] Embodiment 5-7 A cuprammonia pure cotton composite fiber nonwoven fabric, which is different from Example 1 in that the usage of the cuprammonia pure cotton composite fiber is different. For specific usage, refer to the table below.

[0037] Table: Usage of copper-ammonia pure cotton composite fiber in nonwoven fabrics of Examples 5-7 Example Usage of cuprammonia pure cotton composite fiber 5 Prepared from Preparation Example 2 6 Prepared from Preparation Example 3 7 Prepared by Preparation Example 4 The samples prepared in Examples 5-7 were taken and tested for liquid absorption and air permeability according to the above test standards, and the test results were averaged.

[0038] Table: Performance test results of Examples 5-7 As can be seen from the above table, the nonwoven fabric samples prepared by Examples 5-6 have a liquid absorption capacity of 13.4-13.6 times, an air permeability of 2196-2204 mm, and good water absorption performance; In Example 7, the liquid absorption is 9.3 times, and the air permeability is 2168mm. It uses ordinary pure cotton fibers without pretreatment process improvement, and the liquid absorption and air permeability have a significant decrease. This may be because in the pretreatment process, the pure cotton fibers are immersed in a mixed solution of isopropanol and bromoethanol. Based on the special chemical properties of the solution, it can effectively interact with the pure cotton fibers to improve their hydrophilic properties; at the same time, it is irradiated under ultraviolet light for 2 hours, and the interaction between the pure cotton fibers and the mixed solution is further enhanced through photochemical reaction, thereby optimizing its water absorption performance; The high-energy nature of gamma rays can further activate the molecular structure of pure cotton fibers, making it easier to combine with other fibers (such as cuprammonia fibers) to form stable composite fibers.

[0039] Example 8 A cuprammonia pure cotton composite fiber nonwoven fabric, which is different from Example 1 in that in the preparation step A2, the spunlace liquid used is pure water.

[0040] Example 9 A cuprammonia pure cotton composite fiber nonwoven fabric, which is different from Example 1 in that, in the preparation step A2, the spunlace liquid used is a mixed liquid with a volume ratio of polyoxyethylene ether: water = 3:2.

[0041] Comparative Example 2 A cuprammonia pure cotton composite fiber nonwoven fabric, which differs from Example 1 in that, in preparation step A2, the fiber web is pre-humidified and then placed in a spunlace processing area to be reinforced and entangled by drum spunlace; wherein the drum spunlace pressure is 8.5 MPa.

[0042] Comparative Example 3 A cuprammonia pure cotton composite fiber nonwoven fabric, which differs from Example 1 in that, in preparation step A2, the fiber web is pre-humidified and then placed in a spunlace processing area, and reinforced and entangled by drum spunlace and flat-net spunlace; wherein the drum spunlace pressure is 8.5 MPa, and the flat-net spunlace pressure is 20 MPa.

[0043] Comparative Example 4 A cuprammonia pure cotton composite fiber nonwoven fabric, which is different from Example 1 in that, in the preparation step A2, the fiber web is pre-humidified, and then placed in a spunlace processing area, and reinforced and entangled by a first drum spunlace, a second drum spunlace, a first flat net spunlace, and a second flat net spunlace; The first drum hydroentanglement pressure is 8.5 MPa, the second drum hydroentanglement pressure is 20 MPa, the first flat mesh hydroentanglement pressure is 12 MPa, and the second flat mesh hydroentanglement pressure is 10 MPa.

[0044] The samples prepared in Examples 8-9 and Comparative Examples 2-4 were taken and the liquid absorption and air permeability tests were performed according to the above test standards, and the test results were averaged.

[0045] Table: Performance test results of Examples 8-9 and Comparative Examples 2-4 As can be seen from the above table, the nonwoven fabrics prepared in Examples 8-9 have a liquid absorption capacity of 13.5-13.9 times and an air permeability of 2226-2231 mm, which is slightly lower than that of Example 1, with Example 8 having the largest drop.

[0046] The nonwoven fabrics prepared by Comparative Examples 2-4 have a liquid absorption of 13.0-13.4 times, an air permeability of 2208-2215 mm, and a further decline in comprehensive performance, which indicates that the selection of the preparation steps and the control of the spunlace parameters have an important influence on the performance of the copper-ammonia pure cotton composite fiber nonwoven fabric. In Example 1, a nonwoven fabric with excellent performance was successfully prepared through the carefully designed preparation steps and parameters, while the different changes in Comparative Examples 2-4 all led to a decline in the performance of the nonwoven fabric. This further verifies the rationality and effectiveness of the preparation method and parameters in Example 1.

[0047] Example 10 A cuprammonia pure cotton composite fiber non-woven fabric, which differs from Example 1 in that an equal amount of silk fibers of the same specifications are used to replace soybean protein fibers.

[0048] Embodiment 11 A cuprammonia pure cotton composite fiber nonwoven fabric, which differs from Example 1 in that an equal amount of bamboo fibers of the same specifications are used to replace the antibacterial zeolite fibers.

[0049] The samples prepared in Examples 10-11 were taken and tested for liquid absorption and air permeability according to the above test standards, and the test results were averaged.

[0050] Table: Performance test results of Examples 10-11 As can be seen from the above table, the samples prepared by Example 10 and Example 11 have a liquid absorption of 12.8-13.2 times and an air permeability of 2197-2210 mm. Compared with Example 1, both properties have decreased to varying degrees. In Example 10, an equal amount of silk fibers of the same specifications replaced soybean protein fibers. Although silk fibers also have good biocompatibility and hygroscopicity, the interaction between soybean protein fibers and the copper-ammonia pure cotton composite fibers and antibacterial zeolite fibers is more ideal in structure, resulting in better performance of the final product. Therefore, after replacing soybean protein fibers with silk fibers, the liquid absorption and air permeability of the non-woven fabric decreased to a certain extent; In Example 11, an equal amount of bamboo fibers of the same specifications replaced the antibacterial zeolite fibers. The bamboo fibers also have excellent moisture absorption and air permeability, but the fiber structure of the antibacterial zeolite fibers may contribute to the overall performance of the non-woven fabric. Therefore, after the antibacterial zeolite fibers are replaced by bamboo fibers, the performance of the non-woven fabric may also be affected to a certain extent. The compatibility and degree of entanglement between fibers are also important factors affecting the performance of nonwoven fabrics. The differences in surface properties and structures between different fibers may lead to different entanglement effects during the hydroentanglement process, which in turn affects the liquid absorption and air permeability of the produced nonwoven fabrics.

[0051] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.

Claims

1. A cuprammonia pure cotton composite fiber, characterized in that: The invention comprises the following components in percentage by mass: 50% pure cotton fiber and 50% cuprammonium fiber, wherein the pure cotton fiber is prepared by the following pretreatment process: S1. Immerse the pure cotton fiber in a mixed solution of isopropyl alcohol and bromoethanol and irradiate it under ultraviolet light for 2 hours; S2. After the irradiation, the pure cotton fiber is fished out and drained, and then exposed to gamma rays for 30 seconds.

2. A nonwoven fabric, characterized in that: The preparation raw materials include the copper-ammonia pure-cotton composite fiber described in claim 1.

3. The nonwoven fabric according to claim 2, characterized in that The invention is prepared from the following raw materials: 25-30% soybean protein fiber, 60-70% copper-ammonia pure cotton composite fiber, and the balance is antibacterial zeolite fiber.

4. The nonwoven fabric according to claim 3, characterized in that The specification of the soybean protein fiber is 1.4dtex*40mm, the specification of the cuprammonia pure cotton composite fiber is 1.6dtex*55mm, and the specification of the antibacterial zeolite fiber is 1.2dtex*35mm.

5. The method for preparing the nonwoven fabric according to claim 3, characterized in that: The method comprises the following preparation steps: A1. Prepare the copper-ammonia pure cotton composite fiber, soybean protein fiber and antibacterial zeolite fiber, and then put them into the opening and mixing machine according to the proportion. After loosening and mixing, put them into the carder for proper carding, and then blow them with strong airflow to form an air duct, so that the various fibers on the carder are peeled off, arranged in three-dimensional irregular patterns and deposited on the net curtain to form a fiber web; A2: The fiber web is pre-humidified and then placed in the spunlace processing area, and is reinforced and entangled through the first, second and third stage spunlace; A3: Dehydrate the spunlace treated fiber web and then dry it.

6. The method for preparing a nonwoven fabric according to claim 5, characterized in that: The spunlace liquid used in A2 is a mixed liquid with a volume ratio of polyoxyethylene ether: water = 2:

3.

7. The method for preparing a nonwoven fabric according to claim 5, characterized in that: In the A2, the first stage of spunlacing is drum spunlacing, the second stage of spunlacing is drum spunlacing, and the third stage of spunlacing is flat mesh spunlacing.

8. The method for preparing a nonwoven fabric according to claim 5, characterized in that: In the A2, the first-stage hydroentanglement pressure is 6.5-8.5 MPa, the second-stage hydroentanglement pressure is 15-20 MPa, and the third-stage hydroentanglement pressure is 10-12 MPa.

9. Use of the nonwoven fabric prepared by the method for preparing the nonwoven fabric according to claim 5 in preparing medical wound dressings and facial mask base fabrics.

Citation Information

Patent Citations

  • Sweat-absorbent non-woven fabric

    CN103696145A

  • Wear-proof and heat-resistant blended yarn and preparing method thereof

    CN107604495A

  • Method capable of enhancing hydrophilic performance of cotton fibers

    CN111485427A

  • Kapok and copper ammonia fiber blended mask cloth and production method thereof

    CN112593342A

  • Improvements in apparatus for use in processing textile fibres

    GB880698A